Two Forms of Palilalia: A Clinicoanatomical Study - M. Ikeda; H. Tanabe (Behavioural Neurology)
The clinical and neuroradiological findings of three patients with marked palilalia due to different neurological disorders are reported. These cases and others in the literature suggest the possibility of different variations. “Spasmodic, heterophonic palilalia” is typically observed in Parkinson's syndrome and pseudobulbar palsy: the content of palilalia is characteristically changed by interruption. “Atonic, homophonic, autoecholalic palilalia” is mainly seen in Pick's disease, and is not affected by external interruption.